2020
DOI: 10.1038/s41598-020-73136-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical characteristics of 77 COVID-19 deaths

Abstract: The COVID-19 outbreak is becoming a public health emergency. Data are limited on the clinical characteristics and causes of death. A retrospective analysis of COVID-19 deaths were performed for patients’ clinical characteristics, laboratory results, and causes of death. In total, 56 patients (72.7%) of the decedents (male–female ratio 51:26, mean age 71 ± 13, mean survival time 17.4 ± 8.4 days) had comorbidities. Acute respiratory failure (ARF) and sepsis were the main causes of death. Increases in C-reactive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 21 publications
0
40
1
2
Order By: Relevance
“…Although biomarker abnormalities must not be confused with definitive diagnosis, they fit well with clinical observations made in patients with COVID-19. Those findings clearly indicated that patients developed signs and symptoms of myocardial infarction, myocarditis, stroke, deep venous thrombosis and subsequent pulmonary embolism, but also gastrointestinal or intracranial bleeding, all contributing to multi-organ disease and failure, and ultimately to fatal outcomes [14] , [15] , [16] , [17] . Single case reports described the occurrence of acute myopericarditis with systolic dysfunction in otherwise healthy middle-aged people on admission for COVID-19, based on an increase in levels of NT-proBNP and high-sensitivity troponin T and confirmed by echocardiography changes and diffuse biventricular myocardial oedema and late gadolinium enhancement on cardiac magnetic resonance imaging [26] , [27] .…”
Section: Evidence For Widespread Endothelial and Myocardial Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…Although biomarker abnormalities must not be confused with definitive diagnosis, they fit well with clinical observations made in patients with COVID-19. Those findings clearly indicated that patients developed signs and symptoms of myocardial infarction, myocarditis, stroke, deep venous thrombosis and subsequent pulmonary embolism, but also gastrointestinal or intracranial bleeding, all contributing to multi-organ disease and failure, and ultimately to fatal outcomes [14] , [15] , [16] , [17] . Single case reports described the occurrence of acute myopericarditis with systolic dysfunction in otherwise healthy middle-aged people on admission for COVID-19, based on an increase in levels of NT-proBNP and high-sensitivity troponin T and confirmed by echocardiography changes and diffuse biventricular myocardial oedema and late gadolinium enhancement on cardiac magnetic resonance imaging [26] , [27] .…”
Section: Evidence For Widespread Endothelial and Myocardial Injurymentioning
confidence: 99%
“…Indeed COVID-19 has emerged as a leading cause of death during the pandemic in this country [13] . People not only died from the primary affection of the lungs, an extensive interstitial pneumonitis and severe acute respiratory distress syndrome (ARDS), but also due to acute cardiovascular events, ventricular fibrillation, heart failure, acute coagulopathies, thrombo-embolic disease, acute kidney and/or liver injury, and multi-organ failure [14] , [15] , [16] , [17] . Besides infecting multiple organs such as the lungs and the heart, SARS-CoV-2 was found causing widespread endotheliitis by entering and infecting endothelial cells inducing massive injury to the vasculature [18] and further augmenting pre-existing organ damage.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Further, laboratory findings of 77 COVID-19 deaths and 852 COVID-19 patients also demonstrated an increase in urea, cardiac troponin, creatine kinase, D-dimer, C-reactive protein (CRP), lactate dehydrogenase (LDH), IL-6, and lower level of lactic acid levels and lymphocytes. 11 , 12 Analysis of 143 cases of COVID-19 revealed a higher level of C-reactive protein, D-dimer, lactate dehydrogenase, serum amyloid, and lower level of albumin are directly associated with developing a critical illness. 9 …”
Section: Introductionmentioning
confidence: 99%
“…As stated above, several comorbidities related to severity and death by covid-19 also are related to hemorheological parameters linked to microcirculatory impairment such as erythrocyte aggregation and erythrocyte deformability. Tissue hypoxia has been reported in death by covid-19 [47]. Hemorheological impairment can lead to a decrease to nutrition and oxygenation of the tissues, leading to hypoxia and a decrease of available nutrients [21][22][23][24].…”
Section: Erythrocyte Behavior and Tissue Hypoxiamentioning
confidence: 99%